Pengaruh Sanksi Perpajakan Dan Pemahaman Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dalam Membayar Pajak Kendaraan Bermotor Di Kota Batam: Sanksi Perpajakan, Pemahaman perpajakan, kepatuhan wajib pajak. - Dian Efriyenty (JURNAL AKUNTANSI BARELANG, 2019)
Motor vehicles every year always increase in Batam City. However, the increase in the number of motorized vehicles was not accompanied by an increase in taxpayer compliance. This research was conducted to examine the effect of taxpayer awareness, taxation sanctions and understanding of taxpayers on taxpayer compliance of individuals in paying motor vehicle tax in Batam City. This research was carried out at the SAMSAT Batam Center Riau Islands Office. The number of samples in this study were 100 respondents with the sampling method using the accidental sampling method. The results of the study showed that the taxpayer awareness variable partially did not affect taxpayer compliance. Variable tax sanctions partially have a significant effect on taxpayer compliance. Taxpayer understanding variables partially have a significant effect on taxpayer compliance. Keywords: Tax Sanctions; Understanding Of Taxpayers; Taxpayer Compliance.